2003
DOI: 10.1161/01.cir.0000097116.29625.7c
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Early Warning Symptoms of Acute Myocardial Infarction

Abstract: Background-Data remain sparse on women's prodromal symptoms before acute myocardial infarction (AMI). This study describes prodromal and AMI symptoms in women. Methods and Results-Participants were 515 women diagnosed with AMI from 5 sites. Using the McSweeney Acute and Prodromal Myocardial Infarction Symptom Survey, we surveyed them 4 to 6 months after discharge, asking about symptoms, comorbidities, and demographic characteristics. Women were predominantly white (93%), high school educated (54.8%), and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
199
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(212 citation statements)
references
References 33 publications
9
199
3
1
Order By: Relevance
“…In diagnosing angina pectoris in women, therefore, physicians must be aware of gender differences in symptom presentation as women present typical angina pectoris complaints less frequently. First of all, angina pectoris in women either does not involve chest pain at all, or the chest pain may be obscured by other complaints [6], [7], such as dyspnoea upon exertion, fatigue, dizziness and nausea. Secondly, if angina pectoris in women does manifest itself by way of chest pain, this pain tends to be less typical and more often an unpleasant feeling somewhere in the chest, which does not disappear within ten minutes in rest nor upon administration of nitroglycerine [8].…”
Section: Angina Pectorismentioning
confidence: 99%
“…In diagnosing angina pectoris in women, therefore, physicians must be aware of gender differences in symptom presentation as women present typical angina pectoris complaints less frequently. First of all, angina pectoris in women either does not involve chest pain at all, or the chest pain may be obscured by other complaints [6], [7], such as dyspnoea upon exertion, fatigue, dizziness and nausea. Secondly, if angina pectoris in women does manifest itself by way of chest pain, this pain tends to be less typical and more often an unpleasant feeling somewhere in the chest, which does not disappear within ten minutes in rest nor upon administration of nitroglycerine [8].…”
Section: Angina Pectorismentioning
confidence: 99%
“…Women were more likely to describe back pain, jaw pain, rest pain, pain related to mental stress, and pain that awoke them from sleep [17,[19][20][21]. Recently, McSweeney et al [22] surveyed 515 women 4 to 6 months post-MI and found that women reported atypical prodromal symptoms including unusual fatigue, sleep disturbance, and shortness of breath, during the month before their MI with only a minority reporting chest discomfort (29.7%). At the time of their MI, 43% of women did not describe any chest discomfort [23].…”
Section: Presentationmentioning
confidence: 99%
“…5,6 This ambiguity is even more pronounced in the female sex and likely relates, at least in part, to the lack of specificity of prodromal symptoms and the atypical clinical presentation in women. 7,8 In a prior retrospective study of STEMI patients undergoing primary percutaneous coronary intervention (PCI) within 6 hours of symptom onset, baseline Q waves emerged as a reliable independent prognostic factor and also proved to be superior to time from symptom onset in predicting 90-day clinical outcomes. 5,9 Interestingly, this electrocardiogram (ECG) metric appeared to be especially advantageous in females.…”
mentioning
confidence: 99%